Role of CX3CR1 receptor in monocyte/macrophage driven neovascularization. - Arun H S Kumar (Public Library of Science (PLoS), 2013)
Monocyte/macrophages are implicated in initiation of angiogenesis, tissue/organ perfusion and atherosclerosis biology. We recently showed that chemokine receptor CX(3)CR1 is an essential regulator of monocyte/macrophage derived smooth muscle cell differentiation in the vessel wall after injury. Here we hypothesised the contribution of CX(3)CR1- CX(3)CL1 interaction to in vivo neovascularization and studied the functional consequences of genetic and pharmacologic targeting of CX(3)CR1 in formation, maturation and maintenance of microvascular integrity. Cells functionally deficient in CX(3)CR1 lacked matrix tunnelling and tubulation capacity in a 3D Matrigel assay. These morphogenic and cytokinetic responses were driven by CX(3)CL1-CX(3)CR1 interaction and totally abrogated by a Rho antagonist. To evaluate the role of CX(3)CR1 system in vivo, Matrigel plugs were implanted in competent CX(3)CR1(+/gfp) and functionally deficient CX(3)CR1(gfp/gfp) mice. Leaky microvessels (MV) were formed in the Matrigel implanted in CX(3)CR1(gfp/gfp) but not in CX(3)CR1(+/gfp) mice. In experimental plaque neovascularization immature MV phenotype was observed in CX(3)CR1(gfp/gfp) mice, lacking CX(3)CR1 positive smooth muscle-like cells, extracellular collagen and basement membrane (BM) laminin compared to competent CX(3)CR1(+/gfp) mice. This was associated with increased extravasation of platelets into the intima of CX(3)CR1(gfp/gfp) but not functionally competent CX(3)CR1 mice. Pharmacologic targeting using CX(3)CR1 receptor antagonist in wild type mice resulted in formation of plaque MV with poor BM coverage and a leaky phenotype. Our data indicate a hitherto unrecognised role for functional CX(3)CR1 in Matrigel and experimental plaque neovascularization in vivo, which may buttress MV collectively in favour of a more stable non-leaky phenotype.